Home Forums SOA Exams School Level Maths Proof 10

Viewing 1 post (of 1 total)
  • Author
  • #23699
    Richard Purvey

      Starting with the two equations:

      1. 1+i=v^(-1) and

      2. (1+i(m)/m)^m=v^(-1), show that lim v→1 i/i(m)=1.



      Re-arranging equation 1. gives i=v^(-1)-1 and re-arranging equation 2. gives i(m)=m*(v^(-1/m)-1), meaning that lim v→1 i/i(m)=lim v→1 (v^(-1)-1)/(m*(v^(-1/m)-1)), which, after using an Online Limits Calculator, is found to equal 1.

    Viewing 1 post (of 1 total)
    • You must be logged in to reply to this topic.